Final Act embodying the results of the Uruguay Round of Multilateral Trade Negotiations, Marrakesh 15 April 1994 (GATT GenevaCH, 1994)
Embodies the results of the negotiations by including the Agreement Establishing the World Trade Organization, the Ministerial Declarations and Decisions, and, the Understanding on Commitments and Financial Services.
Additional copy located in the Secretary-General's office